Management accounting and economic security in corporate management of agricultural company operation - Ostaev, Gamlet Y.; Alborov, Rolan A.; Ermakov, Dmitry N.; Belokurova, Elena V.; Artemiev, Nikolay V. (Journal of the University of Zulia, 2022)
The article analyzes management accounting and economic security in the corporate governance system of an agricultural organization in an integrated manner, regarding the study of internal and external factors. The objective of the study is to develop an accounting model in business management, taking into account business development and economic security. In accordance with this objective, the main task was determined, to develop a comprehensive mechanism in terms of business development, resource conservation, production, budgeting and economic security. To develop an accounting model in business management, taking into account business development and economic security, the parameterization method was applied by modeling situations under modern conditions. The need to apply a systematic approach is founded, monitoring indicators are proposed to determine the risks and various threats to the operation and development of a business.